PEMANFAATAN AIR TANAH JAKARTA - Samsuhadi, Samsuhadi (Center for Environmental Technology, 2009)
The Jakarta groundwater is one of the water resources in which people rely on it in great deal. With the limitation of the Water Supply Company to serve its user, groundwater becomes very valuable and dependable resource. The magnitude of extraction reaches out above itÃ¢â‚¬â„¢s save yield. In the year of 2002 about 1230 to 1590 millions cubic meters water were accumulated from precipitation. Approximately of 1027 million cubic meters each year about to be consumed by the people of Jakarta. The groundwater consumption tend to increase while the land capability to absorb groundwater decreasing as the land development expanding. Hidrologically the hydraulic conductivity of the Jakarta groundwater aquifer system is very low, so that the groundwater flowrate from the south region of Jakarta basin is also low. With the magnitude of extractionÃ¢â‚¬â„¢s very havily, the cone of depression incident has been occurring in the north Jakarta region. Along with this incident, a land subsidence was also occurring in the neighboring area. To overcome these problems, the assessment of the artificial recharge to the Jakarta aquifer particularly at the critical locations has been done. Schemes of the artificial recharges were simulated. Locations and magnitudes of these schemes were recommended to prevent further depression and saltwater intrusions.Ã‚Â Key words : groundwater, aquifer, basin Jakarta, simulation, artificial recharge.